Socio-economic modernization of the Republic of Kazakhstan as a factor of economic development (Journal of Economic Research & Business Administration, 2016)
Implementation of strategic priorities and reforms in Kazakhstan areaimed primarily at the development of social and economic institutions ofthe country. And socio-economic modernization as the coming decades willbe the most important direction of Kazakhstan. Today in the world crisis ofproduction factors and international policies adversely affect many States.Kazakhstan’s economy will achieve good results in the future if successfullyimplementing structural reform of the market economy. The developmentand establishment of market economy in our country has long been thefocus of activity of any enterprise meeting the needs and requirements ofthe buyers. All firms, not realized in time the priority of this production, areunable to resist in today’s competitive environment. In this regard, the presentarticle describes peculiarities of socio-economic modernization. Also,the article discusses the experience of foreign countries for study and use inpractice the principles and techniques of economic development, recommendationsfor the development of enterprise strategies.
Keywords: socio-economic modernization; economic development; agriculture; differentiation strategy; innovation strategy.